Efforts of Government Institutions to Support Exclusive Breastfeeding Among Civil Servants - Batjo, Siti Hadijah; Hadiha, Hadina; Muliani, Muliani; Radjulaini, Zakiah (Poltekkes Kemenkes Palu, 2023)
Exclusive breastfeeding rate in Palu City has decreased in the last three years from 59.9% (2018) to 57.8% (2019) and 52.42% (2020). Work caused failure to provide exclusive breastfeeding among women. This study aims to explore the efforts of government institutions to support exclusive breastfeeding among civil servants in Palu City, Central Sulawesi. This study applied a qualitative approach, constructivism paradigm, and phenomenological strategy. The study subjects were selected according to the study objectives, which involved the main informants namely the heads of health department; women's empowerment and child protection department, education department, employment department, social affairs department and head of the Religious Office. In addition, there were key informants, namely civil servants with babies aged <12 months who had breastfed or were currently breastfeeding. The number of study subjects was considered sufficient when the coding results and data categories obtained were saturated. Triangulation was carried out towards the Mayor of Palu. Data were collected through in-depth interviews based on interview guides. All interviews were recorded using an audio recorder. The main instrument in this study was the researchers. Ethical Clearance letter Number: 0042/KEPK-KPK/V/2022 dated June 7, 2022 was issued by the Ethics Commission of Palu Health Polytechnic. The results revealed that breastfeeding rooms in the workplace were not yet available for breastfeeding women; there was no reduction in working hours for breastfeeding women, the workload for breastfeeding women was the same, and there was no specific support or motivation from the leaders, and no one had ever provided rewards. Furthermore, the triangulation towards the Mayor of Palu revealed that he promised to make a Regional Regulation (PERDA) that women who exclusively breastfeed will be given leave for 6 months. It can be concluded that the government institutions had not provided support for civil servants to perform exclusive breastfeeding. To achieve the target of exclusive breastfeeding, the government must support exclusive breastfeeding.